Evaluating functional C1INH with multiple laboratory methods across Hereditary Angioedema types - Bardou, Maine Luellah Demaret; Constantino-Silva, Rosemeire Navickas; Alonso, Maria Luiza Oliva; Teixeira, Ana Júlia Ribeiro; Giavina-Bianchi, Pedro Francisco; Mansour, Eli; Pesquero, João Bosco; Valle, Solange Oliveira Rodrigues; Grumach, Anete Sevciovic (Frontiers in Immunology, 2025)
IntroductionHereditary Angioedema (HAE) is a rare genetic disease characterized by recurrent episodes of edema and classified into HAE with C1 inhibitor deficiency (HAE-C1INH types 1 and 2) and HAE with normal C1INH (HAE-nC1INH). This study evaluates the function of C1 inhibitor (fC1INH) in patients with suspected HAE using several laboratory methods: dried blood spot (DBS), chromogenic assay, and ELISA with FXIIa and PKa (plasma kallikrein). The comparative approach aims to improve early detection and understanding of C1INH dysfunction in all HAE subtypes to reflect real-world diagnostic scenarios.MethodsWe assessed the diagnostic performance of four fC1INH assays in a cohort of 148 HAE patients: 84 with HAE-C1INH (72 type 1 and 12 type 2) and 64 with HAE-nC1INH (53 HAE-FXII and 11 HAE-UNK). The gold-standard chromogenic assay and the two substrate-specific ELISAs (PKa and FXIIa) were compared to a novel DBS-based LC-MS/MS assay using endogenous C1s activity. For all fC1INH assays, values >50% were considered within the normal range.ResultsIn HAE-C1INH, the DBS assay showed the highest specificity (type 1: 98.6%, type 2: 100%) and 100% sensitivity for both subtypes. ELISA-FXIIa also performed well (specificity: 97.2% and 91.7%). In contrast, ELISA-PKa and the chromogenic assay showed reduced specificity in type 2 (25% and 66.7%, respectively). Among patients with HAE-FXII, fC1INH levels were reduced by 36.5% by ELISA-FXIIa (19/52), 19.1% by DBS (9/47), and 3.8% by ELISA-PKa (2/52), and no alterations were detected by the chromogenic assay. Some of the changes seen in other tests may be partly related to pregnancy in a few patients. In the HAE-UNK group, all 11 patients had fC1INH >50% in all methods.ConclusionDBS-based LC-MS/MS and ELISA-FXIIa offer promising accuracy and broader applicability for early diagnosis of HAE types 1 and 2. The use of novel substrates and the inclusion of a clinically realistic cohort may enhance the translational relevance of these findings.